2007
DOI: 10.1007/s00167-007-0453-2
|View full text |Cite
|
Sign up to set email alerts
|

The surgical outcome of immediate arthroscopic Bankart repair for first time anterior shoulder dislocation in young active patients

Abstract: This study evaluated the surgical outcomes of young active patients with arthroscopic Bankart repair within 1 month after first-time anterior shoulder dislocation. From July 2002-October 2004, patients presented with first-time traumatic anterior shoulder dislocation and treated with arthroscopic stabilization within 1 month of injury were retrospectively reviewed. Magnetic resonance imaging and computed tomography were performed before the operation in all cases. Cases with contralateral shoulder multidirecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 21 publications
6
51
0
5
Order By: Relevance
“…Kim et al [10] reported that a series of 167 patients who underwent arthroscopic Bankart repair had an average final ASES score of 91.9, with 78% of patients having an excellent Rowe score and a 4% rate of recurrent instability at 2-to 6-year followup. Another series by Law et al [13] of 38 patients with an average age of 21 years at mean 28 months after arthroscopic Bankart repair for anterior shoulder instability recorded an average WOSI score of 83%, which is similar to our mean WOSI of 86.8%. In a series of 18 patients with a mean age of 26.8 years, Marquardt et al [16] reported a mean ASES score of 92.1 at mean 8.7 years after surgery.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Kim et al [10] reported that a series of 167 patients who underwent arthroscopic Bankart repair had an average final ASES score of 91.9, with 78% of patients having an excellent Rowe score and a 4% rate of recurrent instability at 2-to 6-year followup. Another series by Law et al [13] of 38 patients with an average age of 21 years at mean 28 months after arthroscopic Bankart repair for anterior shoulder instability recorded an average WOSI score of 83%, which is similar to our mean WOSI of 86.8%. In a series of 18 patients with a mean age of 26.8 years, Marquardt et al [16] reported a mean ASES score of 92.1 at mean 8.7 years after surgery.…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of recurrent instability in our study seems comparable to other published series of arthroscopic instability procedures in which a simple sling was used [10,13,16], but without a head-to-head comparison in the setting of a single study, this inference should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 84%
“…In people younger than 25 years of age, the recurrence rate following conservative management has been reported to be between 60 and 90% [37]. Therefore, there is an increasing trend to treating this group of patients operatively, even after their first traumatic anterior shoulder dislocation [38][39][40]. Contraindications to surgical treatment may include brachial plexus and axillary nerve injuries, deltoid dysfunction and infections [14].…”
Section: Surgical Management Of Glenohumeral Instabilitymentioning
confidence: 99%
“…In the past decade, while more and more studies investigated the pathologies and treatment, ten types of SLAP lesions have been identified [3,12,15,17,18]. Among the ten types of SLAP lesions, type II lesion is the most common one, which is defined by ''superior labral fraying with stripping of the superior part of the labrum and attached biceps tendon from the underlying glenoid cartilage'' [3,17].…”
Section: Introductionmentioning
confidence: 99%